ENDOSCOPIC AND HISTOPATHOLOGICAL CHARACTERISTICS OF GASTRIC LESIONS SUSPECTED OF EARLY GASTRIC CANCER AND PRECANCEROUS LESIONS (Tạp chí Y học Cộng đồng, 2026)
Objective: To describe the endoscopic and histopathological characteristics of gastric lesions suspected of early gastric cancer and precancerous lesions.Methods: A cross-sectional study was conducted on 200 patients with gastric lesions detected on endoscopy at 108 Military Central Hospital from 2020 to 2024. All patients underwent magnifying narrow-band imaging (NBI) endoscopy and chromoendoscopy. Lesions suspected of early gastric cancer according to Japanese endoscopic criteria were biopsied for histopathological diagnosis.Results: Most lesions had a size ≤ 1 cm (51.0%). NBI endoscopy showed that 51% of lesions had no clear demarcation line; nearly half exhibited a homogeneous microsurface pattern and regular microvascular pattern. Thirty-five lesions suspected of early gastric cancer were biopsied; histopathology revealed early gastric cancer in 42.9%, high-grade dysplasia in 34.2%, low-grade dysplasia in 17.1%, and chronic inflammation in 5.8%. Among the 35 lesions suspected of early gastric cancer on endoscopy, 94.2% were confirmed as early gastric cancer or precancerous lesions on histopathology.Conclusion: This study shows that early gastric cancer and precancerous gastric lesions present with diverse endoscopic appearances and histopathological patterns.
Keywords: Early gastric cancer; Gastric precancerous lesions; Histopathology.